2014
DOI: 10.1002/cam4.351
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of NDUFB6 due to 9p24.1‐p13.3 loss is implicated in metastatic clear cell renal cell carcinoma

Abstract: This study was conducted to clarify the genomic profiles of metastatic clear cell renal cell carcinomas (ccRCCs) and identify the genes responsible for development of metastasis. We analyzed the genomic profiles of 20 cases of primary ccRCC and their corresponding metastases using array-based comparative genomic hybridization, and identified 32 chromosomal regions in which gene copy number alterations were detected more frequently in metastases than in the primary tumors. Among these 32 regions, 9p24.1-p13.3 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Association analysis with clinicopathological features found that NDUFB6 may be a new biomarker of metastasis (Table 1). A recent study showed that NDUFB6 is a possible tumor suppressor of metastatic clear cell renal cell carcinomas (Narimatsu et al, 2015). NDUFB6, a component of respiratory chain complex I (RCI), is located in the mitochondria (Loublier et al, 2011) and plays an important role in electron transfer activity (Dieteren et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Association analysis with clinicopathological features found that NDUFB6 may be a new biomarker of metastasis (Table 1). A recent study showed that NDUFB6 is a possible tumor suppressor of metastatic clear cell renal cell carcinomas (Narimatsu et al, 2015). NDUFB6, a component of respiratory chain complex I (RCI), is located in the mitochondria (Loublier et al, 2011) and plays an important role in electron transfer activity (Dieteren et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…NDUFB6, a component of respiratory chain complex I (RCI), is located in the mitochondria (Loublier et al, 2011) and plays an important role in electron transfer activity (Dieteren et al, 2011). RCI dysfunction may contribute to tumor progression by enhancing the metastatic potential of tumor cells (Narimatsu et al, 2015). Clinical study has indicated that downregulation of NDUFB6 was implicated in poor prognosis of clear cell renal cell carcinomas (Narimatsu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of highly connected potential hub genes from the gene co-expression network should facilitate the identification of candidate biomarkers and therapeutic targets for colorectal cancer. Among 10 putative hub genes (Table 1 , Figure 7 ), all 5 upregulated hub genes have been identified as oncogenes [ 40 , 53 59 ], and all 5 downregulated hub genes have been identified as tumor suppressor genes [ 60 64 ]. MTHFD1L is the only hub gene which has both positive and negative correlations with genes pertaining to cell cycle and lipid metabolism respectively (Figure 7A ).…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumors of RCC were surgically resected at Oita University Hospital and Oita Red Cross Hospital (Oita, Japan) and diagnosed histopathologically as described previously (Table S1). Use of the tissue samples for all experiments was approved by the Oita University Ethics Committee (approval no.…”
Section: Methodsmentioning
confidence: 99%